The value of the expression x2−5x+4 when x=−3 is, (−3)2−5×−3+4=9+15+4=28
True
False
x2−5x+4 when x=−3 is found by substituting x = -3 in the expression. (−3)2−5×−3+4=9+15+4=28 Therefore, the statement is true.
The value of following expression when x=−3,
x2 − 5x + 4 gives (−3)2 − 5 (−3) + 4 = 9 + 15 + 4 = 28
The value of following expression when x = 3,x2 − 5x + 4 gives (−3)2 − 5 (−3) + 4 = 9 + 15 + 4 = 28
Substituting x=−3 in x2+5x gives 32+5(−3)=−9−15=−24.
Find and correct the errors in the following mathematical statement. Substituting x = −3 in
(a) x2 + 5x + 4 gives (−3)2 + 5 (−3) + 4 = 9 + 2 + 4 = 15
(b) x2 − 5x + 4 gives (−3)2 − 5 (−3) + 4 = 9 − 15 + 4 = −2
(c) x2 + 5x gives (−3)2 + 5 (−3) = −9 − 15 = −24